Positioning Head Tilt in Canine Lysosomal Storage Disease: A Retrospective Observational Descriptive Study - Tamura, Shinji; Tamura, Yumiko; Nakamoto, Yuya; Hasegawa, Daisuke; Tsuboi, Masaya; Uchida, Kazuyuki; Yabuki, Akira; Yamato, Osamu (Frontiers in Veterinary Science, 2021)
Positioning head tilt is a neurological sign that has recently been described in dogs with congenital cerebellar malformations. This head tilt is triggered in response to head movement and is believed to be caused by a lack of inhibition of the vestibular nuclei by the cerebellar nodulus and ventral uvula (NU), as originally reported cases were dogs with NU hypoplasia. We hypothesized that other diseases, such as lysosomal storage diseases that cause degeneration in the whole brain, including NU, may cause NU dysfunction and positioning head tilt. Videos of the clinical signs of canine lysosomal storage disease were retrospectively evaluated. In addition, postmortem NU specimens from each dog were histopathologically evaluated. Nine dogs had five lysosomal storage diseases, two Chihuahuas with neuronal ceroid lipofuscinosis (NCL), two Border Collies with NCL, one Shikoku Inu with NCL, two Toy Poodles with GM2 gangliosidosis, and two Shiba Inus with GM1 gangliosidosis. Twenty-eight movies recorded the clinical signs of the dogs. In these videos, positioning head tilt was observed in two Chihuahuas with NCL, one Border Collie with NCL, one Shikoku Inu with NCL, one Toy Poodle with GM2 gangliosidosis, and two Shiba Inus with GM1 gangliosidosis. Neuronal degeneration and loss of NU were histopathologically confirmed in all diseases. As positioning head tilt had not been described until 2016, it may have been overlooked and may be a common clinical sign and pathophysiology in dogs with NU dysfunction.